Ideea de bine comun și criza sistemelor simbolice de interpretare a lumii în Țiganiada lui Ioan Budai-Deleanu - Mianda Cioba (Revista de Istorie și Teorie Literară)
This paper aims to once more address the issue of ideological connections and textual lineages which place the work of Ioan Budai-Deleanu in the hypertext of the eighteenth century European culture, an approach that critical analysis often undertook exclusively from the perspective of free and subjective dialectics of text perception. In this case, however, the examination of the textual tradition starts from stipulating an intentio auctoris which, in the opinion of E. D. Hirsch (1967), is leading to the work of art’s meaning, a semantic reality different from the one named significance, configured in the reading process. Central to this argument is the idea that the authorial intention is responsible for the work’s unity and semantic coherence, illustrated by the subordination of the first part of the poem, a panoramic view of epic-heroic genres treated in the burlesque key, to the second (chants X–XII) containing an objective debate on the values of civil life and optimal methods of governance. The debate in the eleventh chant is performed under the direct influence of some famous political philosophy texts (due to Aristotle, Marsilius of Padua, Alonso de Madrigal, and Juan Huarte de San Juan), whose direct undistorted echoes are easy to be seen in the way the author develops the concept of common good. The object of the discourse is the res publica and the principles that define good governance. What kind of individuals requires the city in order to prosper, which attributes of human nature – those are very old questions we can retrieve beginning with the medieval dispute between poetry and philosophy, especially in the early European modernity’s complex rivalry between artes and disciplinae, between orators and jurists. Beyond the many factitious oppositions that can be drawn from it, his philosophical and legal culture, as well as his temperament critically inclined towards the exercise of a demystifying rationality, places Țiganiada’s author on the side of those who feel that a deep understanding of human nature and the relationship between this nature and social dynamics constitute primordial values of any given political community’s existence.